Analisis Kualitas Pelayanan terhadap Tingkat Kepuasan Pelanggan Pengguna Jasa J&T Express Bandung Kulon, Kota Bandung - Rismayanti Rismayanti; Tiris Sudartono (Syntax Idea)
The focus of this research is service quality on customer satisfaction at J&T Bandung Kulon, Bandung City. This research is motivated by the existence of a relationship between the two variables based on several previous studies. As for service quality, there are 5 (five) variables in it, namely: Reliability Variable, Direct Evidence Variable, Responsiveness Variable, Assurance Variable, and Empathy Variable. For service quality, there are 3 (three) variables in it, namely: Service Indicator, Enterprise Satisfaction, and Product or Service Satisfaction. This study uses a qualitative descriptive method. The purpose of this study was to analyze the relationship between service quality and customer satisfaction at J&T Bandung Kulon, Bandung City. Respondents in this study amounted to 22 people and data were collected through interview techniques. The results of this study are that in terms of service quality, J&T Express Bandung Kulon still needs to make improvements in terms of the shuttle service. Then in terms of customer satisfaction it is still relatively low from the results of the interviews conducted